Apache Kafka Complete Developer's Guide - Stashchuk, Bogdan (Packt Publishing, 2020)
Learn core Apache Kafka features along with creating Java, Node.js and Python producers and consumers About This Video Understand how Apache Kafka works and its core features Build custom Apache Kafka producers and consumers using native Java API Learn and practice how to run multiple brokers on the same computer In Detail Explore an interactive and easy way to learn Apache Kafka with this practical guide. Featuring interesting activities to help you build projects using APIs for programming languages such as Node.js and Python, this course will ensure you get hands-on experience. You will learn how Apache Kafka works and also understand its core features. After delving into the architecture of Kafka, you will focus on how to build custom Apache Kafka producers and consumers using native Java API. The course will gradually assist you in working through a variety of activities related to Apache Kafka, from creating a cluster with multiple brokers and developing topics with replication factors, through to launching the performance monitor for testing the performance of consumers and producers. The course will also demonstrate how to use Apache Kafka API to create your own consumers and producers using Python and Node.js. By the end of this course, you'll be well-versed with Apache Kafka and have the skills and confidence you need to build projects using it.